2007
DOI: 10.4049/jimmunol.179.1.655
|View full text |Cite
|
Sign up to set email alerts
|

Apis Mellifera Venom and Melittin Block neither NF-κB-p50-DNA Interactions nor the Activation of NF-κB, Instead They Activate the Transcription of Proinflammatory Genes and the Release of Reactive Oxygen Intermediates

Abstract: Many alternative treatment approaches, originating from Asia, are becoming increasingly popular in the Western hemisphere. Recently, an article published in a renowned journal reported that venom of apis mellifera (bee venom (BV)) and melittin mediate immune-modulating effects by blocking the activation of the transcription factor NF-κB. Such a modus operandi would corroborate the many claims of beneficial effects of BV treatment and give immediate credit to this form of therapy. Fibroblast-like synoviocytes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 38 publications
6
51
0
1
Order By: Relevance
“…Interestingly, we found that melittin does not inhibit TNF-α-or IL-1β-induced MMP3 expression, or NF-κB activity (data not shown). These results are consistent with a recent report that melittin does not decrease NF-κB activity induced by IL-1β or TNF-α (15). Taken together, these results suggest that melittin inhibits LPS-mediated FLS activation by acting on a signaling pathway that LPS does not share with IL-1β or TNF-α.…”
supporting
confidence: 82%
“…Interestingly, we found that melittin does not inhibit TNF-α-or IL-1β-induced MMP3 expression, or NF-κB activity (data not shown). These results are consistent with a recent report that melittin does not decrease NF-κB activity induced by IL-1β or TNF-α (15). Taken together, these results suggest that melittin inhibits LPS-mediated FLS activation by acting on a signaling pathway that LPS does not share with IL-1β or TNF-α.…”
supporting
confidence: 82%
“…This peptide has a highly cytotoxic effect on different types of cells, mostly due to disruption of the cell membrane. Namely, melittin shares its amphipathic properties with a series of peptides that affect the cell membrane bilayer integrity, either by creating defects, disrupting it, or by forming pores (44).…”
Section: Discussionmentioning
confidence: 99%
“…EMSA-Preparation of nuclear extract, execution of EMSA, and EMSA specificity control experiments have been described in detail on a number of occasions (16,19,20). In short, oligonucleotides resembling consensus binding sites for NF-B (5Ј-AGT TGA GGG GAC TTT CCC AGG C-3Ј), AP-1 (c-Jun) (5Ј-CGC TTG ATG AGT CAG CCG GAA-3Ј), and CRE (5Ј-AGA GAT TGC CTG ACG TCA GAG AGC TAG-3Ј)) were purchased from Promega (Promega, Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…A number of additional controls (competition and supershift assays) for EMSAs utilizing the consensus NF-B elements have been shown before (17,19). Parts of such control experiments are also shown in Fig.…”
Section: Double-and Single-stranded Rna Analogs Activate Nf-b In Fls-mentioning
confidence: 99%